A Comparative Study of the Calligraphic Rules of Muhammad Shawqi and Hashim Muhammad Al-Baghdadi in the Naskh Script - Sumardi, Sumardi; Zulhelmi, Anshar; Zulkhairi, Zulkhairi; Syahruddin, Hisyam; Fajri, Akmal (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2025)
This This study compares the calligraphic rules of two renowned Arabic calligraphers, Muhammad Shawqi and Hashim Muhammad Al-Baghdadi, with a focus on their treatment of the Naskh script. Using a comparative qualitative approach, the research analyzes their methods for forming both isolated and connected letters. The findings highlight key stylistic differences: Shawqi favored elongated, intricate letterforms suited for high-quality manuscript production, while Al-Baghdadi employed a simplified and systematic style aimed at educational accessibility. Despite these differences, both shared pedagogical practices, such as beginning lessons with the prayer